Structures of Black American Individuality and Philosophy for Musicians and their Listeners (International Journal of Innovative Research in Engineering & Management, 2023)
Rock music and acetabular society are a  contentious place within modern culture, with individuals  of the dominant mainstream typically stigmatizing them as  an outgrowth of intrinsic gang as well as drug culture.  Popular music and hip-hop movement occupy a  contentious territory in modern American society. But in  the other hand, this dismissal ignores the complicated  political, socioeconomic, and geopolitical factors that have  influenced the development and expansion of this form of  creative expression. This essay argues that rock music is a  resistant profession that allows disenfranchised Black  American adolescents to express views and concerns that  are frequently ignored by the dominant cultural, but that it  therefore contributes significantly to Black American  personalities and culture. The authors critically investigate  the concept of "culture" in cognitive science,  misinterpreting it via a postmodern lens that considers the  influence of control, domination, and rejection in culture  production. In order to support that viewpoint.
Keywords: Cultural; Expression; Occupational Science; Postcolonial; Resistance